Analysis of Implementation of Internal Control System in Planning and Budget Implementation at UPTD Puskesmas in Tanjung Jabung Timur District - Satria, Darma (Program Studi Farmasi UNAJA, 2022)
This study aims to analyze the implementation of Internal Control System in the planning and implementation of budget, constraints and solutions of the implementation of Internal Control System in the planning and implementation of budget at UPTD Puskesmas in Tanjung Jabung Timur district. The study was conducted at 17 puskesmas by using qualitative descriptive method. Primary data were collected through questionnaires, interviews and observations. Secondary data is collected from relevant documents. The results of the analysis show that budget planning at puskesmas level is good enough. Implementation of Internal Control System in budget planning at UPTD Puskesmas in general is in category quite effective with result of calculation equal to 53,04%. Implementation of BOP activities at UPTD puskesmas is done based on the Plant Of Action that have been prepared and submitted to each program manager. Although in general the application of internal control system in the planning and execution of budget has been running quite effective, but there are still elements of internal control that has not run properly ie the information and communication elements. Information and communication in the planning and implementation of the budget is only 20.59% and 38.24%. This condition is caused by the absence of information technology in planning and budget implementation at UPTD puskesmas.